2001
DOI: 10.1093/oxfordjournals.jbchem.a002823
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Queuosine Synthesizing Enzyme, tRNA-Guanine Transglycosylase, and Queuosine Levels in tRNA of Leukemic Cells

Abstract: Queuosine is a modified nucleoside located at the first position of the tRNA anticodon, which is synthesized by tRNA-guanine transglycosylase (TGT). Although the levels of queuosine in cancer cells have been reported to be lower than those in normal cells, the expression levels of TGT remain to be determined. We determined the expression levels of a subunit of TGT (TGT60KD). Contrary of our expectations, the results revealed higher levels of expression of TGT60KD than that in normal cells, and the level of que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…To date, only a few studies have implicated USP14 in cancer [15–17], and to the best of our knowledge, this is perhaps the first report demonstrating the role of USP14 in lung adenocarcinoma. Previous studies showed that USP14 protein and mRNA levels were dysregulated in patients with more aggressive tumors of leukemia, colon cancer, and intrahepatic cholangiocarcinoma [15–17].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…To date, only a few studies have implicated USP14 in cancer [15–17], and to the best of our knowledge, this is perhaps the first report demonstrating the role of USP14 in lung adenocarcinoma. Previous studies showed that USP14 protein and mRNA levels were dysregulated in patients with more aggressive tumors of leukemia, colon cancer, and intrahepatic cholangiocarcinoma [15–17].…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies showed that USP14 protein and mRNA levels were dysregulated in patients with more aggressive tumors of leukemia, colon cancer, and intrahepatic cholangiocarcinoma [15–17]. These papers are very important because they provide evidence that USP14 is implicated in cancer biology.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Queuine functions as a growth modulator for higher eukaryotes that significantly reduces overall protein synthesis in mammalian cells, and modulates the phosphorylation of specific proteins 4. Queuine deficiency has been observed in tRNAs from ovarian tumors,5 whereas increased levels of Q have been observed in human leukemic cells 6. Here, we report the crystal structure of TM0574, that was determined using the semiautomated, high‐throughput pipeline of the Joint Center for Structural Genomics (JCSG) 7…”
Section: Introductionmentioning
confidence: 97%
“…Along these lines, mutants in Q-base synthesis in Shigella have been shown to exhibit reduced virulence, a phenotype associated with reduced translation of the virulence factor VirF (14). This phenotype is akin to the requirements for Q-base synthesis in some cancerous cells (15), a fact that was recognized early on. In any event, final assignment of the function of this modification will ultimately require settling the question of whether YadBmediated glutamylation extends to other Q-base-containing tRNAs, such as tRNA His and tRNA Tyr .…”
mentioning
confidence: 99%